An anger management programme as an action learning set. (2nd September 2019) - Shepherd, Gary
ABSTRACT: Reports of anger and aggression within the general population of the UK have been on the increase since the 2008 financial crisis. Traditional anger management programmes utilise Cognitive Behavioural and Mindfulness theory within a psychoeducational setting to help angry participants adapt and change their behaviours. These approaches have a mixed success rate and have led researchers to call for anger management programmes to adopt different methodologies. This account of practice describes a different anger management programme which incorporates the action learning cycle within its weekly structure. Utilising thematic analysis, the author reflects upon the way in which participants responded to this new approach and considers the promise and limitations of using action learning within future anger management programmes.